An Investigation of the Students Attitude towards Introductory Computer Course at Bauchi Metropolitan Universities: An Undergraduates Survey - Gololo, Ibrahim Aliyu (American Finance & Banking Review, 2017)
This study investigates the students‟ attitude on the introductory computer course at Bauchi Metropolitan University. Bauch State is one of the 36 States in Nigerialocated in the North East Region of the country with only Two Public Universities, ATBU and BASUG. Inboth universities it is mandatory for students to undertake introductory computer course in their first year entry to the university and this research was conductedwith the aim to find out the students attitude toward the computer course as part of the requirement to their studies. This study uses a sample of 300 undergraduate students (male=188, female=110) students. Primary data were utilized where questionnaire was employ as the tool of data collection. Computer attitude related questionnaire was developed and administered to the respondents and retrieved. Frequencies and Percentages was used to analyzed the respondents demographic information and questions asked while the chi-square X2 analysis was employ to test the stated hypothesis. The result of this study shows that students had positive attitude toward introductory computer course as the calculated chi-square X2c 0.253 which is less than the tabulated chi-square X2t of 3.841i.e. X2c < X2t therefore the study conclude that students had significant and positive attitude toward introductory computer course at Bauchi metropolitan university and we recommends that priority attention in terms of computer practical session should be given to students to increase their likeness of the computer and adequate arrangements should be made by universities to ensure students have access to computer and the internet whenever needed within the campus area and this will also mould a positive attitude for students.